Modern receiver front-ends : systems, circuits, and integration - Laskar, Joy (Wiley-Interscience, 2004)
Architectures BABAK MATINPOUR and JOY LASKAR* Describes the actual implementation of receiver architectures from the initial design to an IC-based product* Presents many tricks-of-the-trade not usually covered in textbooks* Covers a range of practical issues including semiconductor technology selection, cost versus performance, yield, packaging, prototype development, testing, and analysis* Discusses architectures that are employed in modern broadband wireless systems.